KOMPETENSI SISWA SMK DALAM MENYONGSONG REVOLUSI INDUSTRI 4.0 - Maryanti, Nova; Apriana, Dina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The background of this research originated from the demands of the industrial revolution 4.0 that all human labor can be replaced with digital machines, so one question arises where do SMK graduates who are ready to work. Transformation efforts to improve efficiency in each value chain by integrating digital capabilities and production lines in the industry which refers to increased automation, machine to machine and human to machine communication, artificial intelligence, and the development of sustainable technology in the industry. In this study we used qualitative methods to collect data on observation, analysis, and documentation of activities. Research focus on class XII (twelve) with 12 an accredited expertise packages for all majors. The results obtained indicate that the creation of skilled students with industry-based competencies, the demands of the industrial world in the industrial revolution era 4.0 are SMK graduates who have the character of discipline, hard work, creative, independent, responsibility, and competency based on the industrial world. Strategies for implementing industry-based education include 1) curriculum links and actives with the industrial world; 2) teaching factoring programs; 3) internships in the industrial world; 4) Expertise Competency Test entirely by Industrial World which has the applicable conditions; 5) professional staff from Industrial World as guest teachers at SMK; and 6) the relevance of vocational facilities and infrastructure to the industrial world. In 2017, the fulfillment of the workforce at PT. Bukit Asam Tbk Tanjung Enim accepts graduates of SMK Negeri 2 Muara Enim as permanent employees of 23 people out of 139 people. This success is a form of collaboration between schools and the Industrial World in creating workers who are ready to work according to the competencies needed by the demands of the industrial world in the era of industrial revolution 4.0.